Consumer Choice: Exploring Factors, Influences and Decisions - Tea Valishvili; Genelidze Lia (ეკონომიკური პროფილი)
In today’s marketplace, creating an effective marketing strategy is more crucial than ever. Technological advancements have significantly influenced consumer behavior, creating a dynamic environment where businesses must adapt to stay competitive. The primary goal of marketing isn’t traditional advertising; it now focuses on building connections between consumers and products. To achieve this, marketers, brands, and businesses need to focus on the consumer decision-making process and the behaviors driving it, enabling them to enhance communication at every stage of the customer journey.